Analisis Pengaruh Geometrik Jalan Terhadap Kecelakaan Lalu Lintas: Analysis of the Influence of Road Geometrics on Traffic Accidents - Ellytrina, Dinda Fauziah Nur; Zhafirah, Athaya (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2022)
The geometric design of the road must comply with the requirements. Otherwise, it will affect the increasing traffic accidents. Traffic accidents are an indicator of road safety. This study aimed to determine the location of accident-prone areas (black spots) and the relationship between geometric road conditions and traffic accidents on the Garut – Tasikmalaya road section via Cilawu. The method used in this research is polynomial linear regression analysis with variable X relationship, consisting of stopping sight distance, overtaking sight distance, bend radius, and degree of curvature. The Y variable is the EAN (Equivalent Accident Number) value. The geometric road data used in this study is primary data directly taken in the field, while traffic accident data is secondary data. The analysis results by calculating the EANc value show that bends one and bends two are the locations of accident-prone areas (black spots). Except for overtaking sight distance, the relationship between road geometry for bend radii, stopping visibility, and degree of curvature to traffic accidents are closely correlated, which means it has quite an effect on accidents. Overtaking sight distance has little effect on accidents.